Arsitektur Vernakular Rumah Lanting Dalam Kajian Ekologi Budaya di Kelurahan Muara Bakanon Kabupaten Murung Raya - Muhammad Rizky Abriazizu; Setia Budhi; Arif Rahman Hakim (Prodi Sosiologi FISIP ULM, 2023)
The Dayak tribe has a unique cultural heritage in the form of buildings on the Barito River namely lanting or floating houses. This study aims to examine the representation of the mutual relationship between humans and nature in the vernacular architecture of the lanting house. This study used a qualitative approach, with a field research types and descriptive research-based. This research was carried out from June to July 2022 in Muara Bakanon Village, Permata Intan District, Murung Raya Regency. Data collection techniques using participant observation, in-depth interviews and documentation. The results of the study show that although the size of the lanting houses in Muara Bakanon Village are different, in terms of the shape of the lanting houses they have not changed much from the past until now. Communities living on the banks of the Barito River build lanting houses as a form of utilizing the river area. In the study of cultural ecology, nature has an influence on culture and human behavior, such as the existence of a lanting house which is a form of adaptation for people living on the banks of rivers which often experience (annual) flooding. Lanting through vernacular architecture is one way to reduce the impact caused by flooding. The community will have no trouble when a flood occurs because the lanting is designed not to be drowned by flood waters. So it can be said that nature has a great influence on people's lives. However, the community in practice has not been able to provide positive benefits to nature, because basically people just use nature for the benefit of survival.